Improving Students’ Learning Result Using Numbered Heads Together Model - Mauliza, Mauliza (International Journal for Educational and Vocational Studies, 2020)
This study aimed to determine the increase in student cognitive learning outcomes within material of occupational health and safety at the laboratory by implementing the Numbered Heads Together model, as well as obtains the students’ perspective toward the implementation of the model. This research was conducted with a quasi-experimental method through one group pretest-posttest design conducted at University of Samudra. Data collection was done by pretest and posttest to find the escalation in cognitive learning outcomes, as well as a questionnaire to determine student responses to the numbered heads together learning model. The average value of N-gain cognitive learning outcomes was 0.51, which was categorized as moderate category; it meant that in general, there was an increase in cognitive learning outcomes of students. Descriptively, students also gave a positive response toward implementation of the Numbered Heads Together model, so it can be concluded that learning with the Numbered Heads Together Model can improve student cognitive learning outcomes.